Evaluation of the Hearing Function in the Orchestra Professional Musicians of the Teatro alla Scala in Milan - Cassina, Terenzio; Tomasin, Alessia; Calcinoni, Orietta; Ambrosetti, Umberto; Filipponi, Eliana; Castelli, Valeria; Bianchin, Riccardo; Teodorani, Valentina; Magnoni, Laura; Braga, Leonardo; Parati, Linda; Di Berardino, Federica (La Medicina del Lavoro, 2025)
Background: This study was conducted to determine whether occupational exposure to high sound levels, typical of an opera orchestra, can cause hearing loss. Methods: The orchestra professors at Teatro alla Scala in Milan underwent ear examinations, pure-tone audiometry, and other audiological tests. The hearing thresholds of these musicians were compared with those of populations not exposed to occupational noise and with populations exposed to industrial noise. Noise exposure levels were estimated through a phonometric survey conducted at our theater in 2011, which largely confirmed the exposure levels outlined in European guidelines. Results: The average audiometric thresholds of the orchestra musicians were slightly worse than the median thresholds of a healthy, non-noise-exposed population. In three subjects (2.8%), bilateral hearing impairment (PTA 0.5, 1, 2, 3, 4 kHz > 25 dB HL) was observed; in four violinists (3.7%) left unilateral hearing impairment was found. This rate is lower than the expected risk from similar industrial noise exposures. Comparing these audiometries with those from about ten years earlier shows that the hearing threshold decline in the study group is comparable to that caused by presbycusis. Conclusions: The risk of noise-induced hearing loss among professional orchestra musicians appears lower than predicted by the UNI ISO 1999:2015 standard. A few cases of hearing loss due to chronic acoustic trauma were noted, particularly among violinists who demonstrated a higher incidence of left unilateral hearing loss. The high levels of sound exposure and the presence of some hearing loss cases highlight the need for targeted preventative measures in this work activity.